Tarkastus, arviointi ja valvonta murroksessa - Kihn, Lili-Anne; Oulasvirta, Lasse; Ruohonen, Janne; Rönkkö, Jaakko; Urpilainen, Matti; Wacker, Jani (Tampere University Press, 2021)
"This book delves into the societally important questions of auditing, evaluation and control that have changed or are expected to change in the 2020s. Changes in the operating environment are constantly shaping the context and regulatory environment of the industry. At the same time, the perceptions of players in the sector about the most appropriate course of action are evolving. The sector and its operators are experiencing a major turning point in many respects. The coronavirus pandemic is an example of a change that has posed new challenges and societal demands to the audit industry, organizations' self-regulating mechanisms, and evaluation. The fifteen articles of this book examine the current phenomena of auditing, control and evaluation practically, but they are also firmly based on scientific research information. The collection is multidisciplinary because the questions examined don't just cross the line between public and private sector, but also between disciplines. It combines empiric, concept analytic and judicial approaches to research. Some of the topics handled in the book are audit of management stewardship, audit oversight, audit of less complex entities, recent audit research results and several topics related to performance evaluation and the paradigm change in evaluation thought. The book is of interest for example to the professionals, students and researchers of auditing and evaluation."